Does Job Embeddedness Mediate the Effects of High-Performance Work Practices on Turnover Intentions? A Study in the Airline Industry - Vatankhah, Sanaz (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2013)
The purpose of this thesis is to develop and test a conceptual model that investigates the effects of high-performance work practices on job embeddedness and turnover intentions. In this model, the mediating role of job embeddedness was also tested. Data were gathered from flight attendants in the three private airline companies in Iran to test the relationships among study variables. These relationships were tested via LISREL 8.30 through structural equation modeling. The results show that the indicators of high-performance work practices (i.e., selective staffing, job security, training, empowerment, rewards, teamwork, career opportunities) increase flight attendants‟ job embeddedness. The results also show that such high-performance work practices reduce flight attendants‟ turnover intentions. The results of this study demonstrate the partial mediating role of job embeddedness between these high-performance work practices and turnover intentions. In this study, management implications are presented and limitations and future research directions are provided. Keywords: Flight Attendants; High-Performance Work Practices; Job Embeddedness; Turnover Intentions

ÖZ: Bu tezin amacı, yüksek performanslı insan kaynakları uygulamalarının iş ile iç içe olma ve işten ayrılma değişkenleri üzerindeki etkilerini araştıran kavramsal bir modeli geliştirip test etmektir. Bu modelde, iş ile iç içe olma değişkeninin aracı rolü de test edilmektedir. Değişkenler arası ilişkilerin test edilebilmesi amacıyla, veri İran‟da faaliyet göstern üç farklı hava yolu işletmesinde çalışan uçuş görevlilerinden toplanmıştır. Analiz kapsamında LISREL 8.30 programı vasıtasıyla yapısal eşitlik modellemesi kullanılmıştır. Bulgular, yüksek performanslı insan kaynakları uygulamalarının (seçici işe alma, iş garantisi, eğitim, güçlendirme, ödüllendirme, ekip çalışması ve kariyer olanakları) uçuş görevlilerinin iş ile iç içe olmalarını artırdığını göstermektedir. Bulgular, aynı zamanda, bu yüksek performanslı insan kaynakları uygulamalarının uçuş görevlilerinin işten ayrılma niyetlerini düşürdüğünü göstermektedir. Bu çalışmanın bulguları, iş ile iç içe olma değişkeninin yüksek performanslı insan kaynakları uygulamaları ile işten ayrılma niyeti arasında kısmi bir aracı rolü olduğunu ortaya koymaktadır. Bu çalışmada, yönetsel belirlemeler üzerinde durulmuş, araştırmanın sınırları ve ileride yapılacak araştırmalar ile ilgili belirlemelere yer verilmiştir. Anahtar Kelimeler: İş ile İçe İçe Olma; İşten Ayrılma Niyeti; Uçuş Görevlileri; Yüksek Performanslı İnsan Kaynakları Uygulamaları
Does Job Embeddedness Mediate the Effects of High-Performance Work Practices on Turnover Intentions? A Study in the Airline Industry
Keywords: Tourism; Employee Motivation - Job Satisfaction - Airline Industry; Flight Attendants; High-Performance Work Practices; Job Embeddedness; Turnover Intentions